A novel biased energy distribution (BED) scheme for clustering sensor networks - Salami, Abdulazeez F.; Anwar, Farhat; Bello-Salau, H.; Aibinu, Abiodun Musa (2011)
This paper presents the impact of utilizing a biased energy distribution (BED) scheme among sensor nodes for clustering sensor networks. In clustering sensor networks, some of the nodes are elected as aggregators and they compress the data from their cluster members before sending the aggregated data to the sink. Existing clustering routing protocols assume that all the nodes are provided with equal amount of energy but this shortens the network lifetime and makes the network unstable once the first node dies. This paper proposes a solution by using a technique that prioritizes the network into higher and lower energy nodes. The aim of this approach is to ensure well balanced energy consumption in order to maximize network lifetime. It is shown by simulation that the proposed technique exhibits better performance when compared to existing clustering routing techniques in terms of throughput, network lifetime and energy consumption.